A randomised, open-label, phase II study of neo/adjuvant doxorubicin and ifosfamide versus gemcitabine and docetaxel in patients with localised, high-risk, soft tissue sarcoma. Issue 13 (September 2015) - Davis, Elizabeth J.; Chugh, Rashmi; Zhao, Lili; Lucas, David R.; Biermann, J. Sybil; Zalupski, Mark M.; Feng, Mary; Wong, Sandra L.; Jacobson, Jon; Zyczynski, Laurie; Reinke, Denise; Metko, Gino; et al.
Abstract Background Doxorubicin and ifosfamide (AI) is standard therapy for high-risk soft tissue sarcoma (STS) but often causes severe toxicities resulting in hospitalisation. Gemcitabine and docetaxel (GD) has efficacy in metastatic STS and may be better tolerated. We conducted a study to compare toxicities and efficacies of these regimens. Methods This open-label, phase II, single institution trial randomised 80 patients with localised, resectable, high grade STS ⩾5 cm to either neo/adjuvant AI or GD. AI was doxorubicin (75 mg/m2) and ifosfamide (2.5 g/m2/d) on days 1–3 with mesna 500 mg/m2/dose. GD was gemcitabine 900 mg/m2 on days 1, 8 and docetaxel 100 mg/m2 day 8. Both arms included filgrastim. The primary end-point was hospitalisation rate. Secondary end-points included disease-free survival (DFS) and overall survival (OS). Results Between November 2004 and August 2012, 80 evaluable patients were randomised, 37 to AI and 43 to GT. In the AI arm, 13/37 (35%) patients were hospitalised versus 11/43 (26%) in the GD arm (p = 0.25). Hospitalisation rates were not significantly different after adjusting for age, gender, location, chemotherapy and number of cycles (p = 0.17). The 2-year and median DFS in the AI arm were 57% and 37 months, respectively, and 74% and not yet reached, respectively, in the GD arm. The most common serious adverse events with AI were haematologic. Metabolic derangements and constitutional symptoms were most common with GD. Conclusions Hospitalisation rate was less with GD but not statistically significant. There was a trend towards longer DFS with GD, and the regimen was tolerable, suggesting GD merits further study. Funding Eli Lilly and Sanofi-Aventis.